IMPLEMENTASI PRINSIP-PRINSIP MANAJEMEN STRATEGI PADA MADRASAH TSANAWIYAH DALAM MEWUJUDKAN MADRASAH YANG BERMUTU - Sutoyo, Sutoyo; Sangad, Sangad; Patimah, Siti Patimah; Wazin, Wazin (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2025)
This study aims to explore the application of strategic management principles in improving the quality of education in junior high schools. The background of the study is the problem of the quality of education in several junior high schools is still relatively low due to minimal institutional management. The location of this study was a junior high school in South OKU Regency. The informants of this study were the head of the school and the vice head of curriculum. The research method used was a qualitative method. Data were collected using interview and documentation techniques. Data analysis used qualitative analysis. The results of the study showed that the principles of strategic management had been applied to the school, but had not been carried out optimally. For example, the principle of planning had been applied well, but in its implementation it was more often not in accordance with the plan. In addition, there were plans that were prepared without using strategic principles so that the education process was only routine and learning evaluation focused on the cognitive domain. Of the three strategic principles, implementation and evaluation are the best strategic management principles applied, while the principle of compiling a strategic plan has not been optimally applied.